2019
DOI: 10.1111/imig.12586
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Migrant Career Success: A Study of Recent Skilled Migrants in Australia

Abstract: Australia has been aggressively pursuing skilled migrants to sustain its population and foster economic growth. However, many skilled migrants experience a downward career move upon migration to Australia. Based on a survey of recent skilled migrants, this study investigates how individual (age, years of settlement, qualifications), national/societal (citizenship and settlement), and organization‐level (climate of inclusion) factors influence their career success. Overall, we found that: (1) age at migration m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 111 publications
(133 reference statements)
0
33
0
Order By: Relevance
“…Some studies suggest that insufficient English proficiency is associated with inadequate labour market integration, including for those with high levels of completed foreign education (Rajendran et al, 2017;Rajendran et al, 2020;Sardana et al, 2016). Other studies based on data collected among recent skilled immigrants from Asia suggest that English skills are an unlikely barrier to labour market success (Derby et al, 2020).…”
Section: Existing Literaturementioning
confidence: 99%
“…Some studies suggest that insufficient English proficiency is associated with inadequate labour market integration, including for those with high levels of completed foreign education (Rajendran et al, 2017;Rajendran et al, 2020;Sardana et al, 2016). Other studies based on data collected among recent skilled immigrants from Asia suggest that English skills are an unlikely barrier to labour market success (Derby et al, 2020).…”
Section: Existing Literaturementioning
confidence: 99%
“…Participants described a range of difficulties securing work common to migrants (including refugees) more generally, such as English-language skills and a lack of local experience, though it was clear that the refugee participants experienced greater barriers to securing work. 26–29,64 Most refugees had been in Australia for varying periods without work rights (some several years), during which time they were unable to gain formal local experience in the labor market nor gain sufficient English-language skills to secure meaningful work—where precariousness can persist. 65 The extreme temporary nature of some visas (three- and six-month duration) provided an additional barrier for the refugee participants, where they felt employers were reluctant to employ them due to their limited residence status.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these studies have shown how company training or mentoring programs and other types of assistance for employees facilitated career success (Choi, 2015; Ng et al., 2005; Yu, 2012). Similarly, other studies have considered how the specific attributes of certain companies – such as size, field of operation, and type of contracts offered – are linked to labour outcomes (Guarnaccia et al., 2018; Rajendran et al., 2020).…”
Section: Determining Factors Of Labour Market Outcomes Among Recently Graduated Studentsmentioning
confidence: 99%